On the Waterfront [videorecording (DVD)] - Kazan, Elia; Brando, Marlon; Malden, Karl; Cobb, Lee J., 1911-1976; Steiger, Rod, 1925-2002; Saint, Eva Marie, 1924- (Marlon Brando DVD collection, 2001)
Terry Malloy is a washed-up ex-prize fighter corrupted along with brother Charley at an early age by a ruthless Mob-connected union boss named Johnny Friendly, who runs the waterfront. Malloy is now an errand-boy for the union, while Charley (in return for a college education) is now a lawyer for them. Malloy assists in the killing of a longshoreman who was talking to the crime commission investigating the union. He soon meets the dead man's agonized sister, Edie Doyle, and has a change of mind. Activist priest Father Barry argues with Malloy about morality, responsibility, and doing the right thing. Malloy's guilt, his romantic feelings for Edie, and an assault on Father Barry overwhelm him and he turns informer. Malloy's defiant testimony before the commission leads to a climactic bloody battle that wrests the union from the boss' tenacious grasp.